1992
DOI: 10.2337/diacare.15.11.1505
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Levels in Community Drinking Waters and Risk of IDDM: An ecological analysis

Abstract: This ecological analysis suggests that low-level nitrate exposure through drinking water may play a role in the etiology of IDDM, perhaps as a promoter through the generation of free radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1
4

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 14 publications
6
53
1
4
Order By: Relevance
“…This may be of particular clinical relevance, since epidemiological studies have demonstrated an increased incidence of IDDM in populations with high intake of dietary nitrites, possibly because of formation of diabetogenic nitrosoamines (Virtanen et al, 1994;Kostraba et al, 1992;Helgason et al, 1982). NO is highly unstable and is readily converted into its stable end products nitrite and nitrate (Bredt and Snyder, 1994).…”
Section: Il-1 Stimulates Islet Nitric Oxide Formation and Causes Apopmentioning
confidence: 99%
“…This may be of particular clinical relevance, since epidemiological studies have demonstrated an increased incidence of IDDM in populations with high intake of dietary nitrites, possibly because of formation of diabetogenic nitrosoamines (Virtanen et al, 1994;Kostraba et al, 1992;Helgason et al, 1982). NO is highly unstable and is readily converted into its stable end products nitrite and nitrate (Bredt and Snyder, 1994).…”
Section: Il-1 Stimulates Islet Nitric Oxide Formation and Causes Apopmentioning
confidence: 99%
“…− ion also causes diabetes and is a precursor of carcinogen [11] [12]. US Environmental Protection Agency (EPA) has set the maximum contamination level as 44 mg/l of 3 …”
Section: Nomentioning
confidence: 99%
“…This finding should be considered in the context of the significance of nitrosamine compounds in the pathogenesis of human Type i diabetes. Analyses of population-based registries of childhood diabetes have revealed an influence of nutrients, among them nitrosamines [18,19]. Why do male LDS mice transmit the tendency to develop insulitis to the next generation.…”
Section: Discussionmentioning
confidence: 99%
“…In group 1, also termed "controls", neither mothers nor fathers were treated with STZ. In group 2, LDS diabetic mothers were (21) 45 + 9 7.3 _+1.5 (19) 19-+9…”
Section: Animalsmentioning
confidence: 99%